IgG4-Related Sclerosing Cholangitis - Nakazawa, Takahiro; Shimizu, Shuya; Naitoh, Itaru (Seminars in Liver Disease, 2016)
More men than women develop immunoglobulin G4-related sclerosing cholangitis (IgG4-SC). Age at clinical onset is significantly older in patients with IgG4-SC. Patients with IgG4-SC appear similar to those with cholangiocarcinoma and primary sclerosing cholangitis (PSC). The association between IgG4-SC and autoimmune pancreatitis (AIP) is useful for the diagnosis of IgG4-SC. However, some IgG4-SC cases are isolated from AIP and are difficult to diagnose. The authors focus on three distinct features of IgG4-SC. First, diffuse inflammation induces a longer stenosis on cholangiography in contrast to the short stenosis of patients with PSC. Second, fibroinflammatory involvement is observed mainly in the stroma of the bile duct wall, whereas the bile duct epithelium is intact. Third, steroid therapy results in remarkable improvement. Although the prognosis of patients with IgG4-SC is good, some cases have developed portal hypertension and liver cirrhosis during their clinical course. Further study is needed to elucidate the long-term outcomes and mechanism of IgG4-SC.
Keywords: immunoglobulin G4-related sclerosing cholangitis; primary sclerosing cholangitis; autoimmune pancreatitis; inflammatory bowel disease; pancreatic carcinoma; cholangiocarcinoma